Knowledge, Preferences, Consumption Behavior of Ultra-Processed Foods and Their Association with Adolescents’ Nutritional Status - Gunawan, Caroline Ferisca; Melani, Vitria; Sitoayu, Laras; Wahyuni, Yulia; Ronitawati, Putri (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
Excessive consumption of ultra-processed foods (UPFs), which are typically high in fat content, and insufficient physical activity may adversely influence adolescents’ nutritional status and lead to abdominal obesity. This condition can occur due to individual’s lack of knowledge and eating preferences, which in turn influence adolescents’ consumption behavior. This research aimed to determine the relationship between knowledge, eating preferences, UPF consumption behavior, and nutritional status among students at Citra Kasih Junior High School, Tangerang. This research was cross-sectional with a sample of 102 students carried out in January 2024. The inclusion criteria were students who were physically healthy, willing to participate, not on a specific diet, and not taking diuretic drugs. Data were analyzed using Pearson and Spearman correlation tests. The results showed most respondents had normal nutritional status (58.8%) and low levels of knowledge about UPFs (53.9%). No significant correlations were found between knowledge, UPF eating preferences, and BMI-for-age, nor between knowledge, UPF eating preferences, UPF consumption behavior, and WHR (p > 0.05). However, a significant correlation was observed between UPF consumption behavior and BMI-for-age (p < 0.05). In conclusion, UPF consumption behavior was significantly correlated with adolescents’ nutritional status based on BMI-for-age.